PROSPEK OMBUDSMAN REPUBLIK INDONESIA DALAM RANGKA MEMPERKUAT PELAKSANAAN EKSEKUSI PUTUSAN PERADILAN TATA USAHA NEGARA - Enrico Simanjuntak (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2014)
The position and function of Administrative Court so weak that the verdict is much neglected. Referring to the approach of the legal system, where the Administrative Court and Ombudsmen of Republic of Indonesia (ORI) equally aims to promote good governance and ensure the legal protection of the public from the actions of public administration law, the ORI is possible to be handed the duties and responsibilities as independent executor PERATUN decision. In the meantime, the Ombudsmen should be given the authority to promote, supervise and impose sanctions against the defendant who is not willing to implement the decision PERATUN or against other parties who obstruct the implementation of the decision PERATUN. Keywords: Administrative Court, Ombudsmen of the Republic of Indonesia, Independet Executor.